An ultra-low hysteresis, self-healing and stretchable conductor based on dynamic disulfide covalent adaptable networks. Issue 4 (10th January 2022) - Kong, Weibo; Yang, Yunyun; Wang, Yanjun; Cheng, Hongfei; Yan, Peiyao; Huang, Lei; Ning, Jingyi; Zeng, Fanhao; Cai, Xufu; Wang, Ming
Abstract : A new strategy to achieve self-healing, anti-hysteresis and stretchable conductors was developed via the design of chemical structures and activity of dynamic bonds in covalent adaptable networks (CANs). Abstract : Stretchable self-healing conductors can autonomously restore their electrical and mechanical properties after experiencing damage, thus being valuable in the application of prostheses, soft robots, and health monitoring. Currently, most reported stretchable conductors are based on supramolecule materials that employ weak dynamic bonds between intermolecular chains to achieve self-healing function. However, these stretchable self-healing conductors encounter an issue of inferior mechanical recovery with large hysteresis. Here, we report a stretchable, self-healing, and ultra-low hysteresis conductor based on a dynamic crosslinked polyurethane polymer using disulfide covalent adaptable networks (CANs). The fabricated polyurethane shows an ultra-low hysteresis degree of 3.8%, a large stretchability of 812% strain, and a high self-healing efficiency of ∼100%. Incorporating with a microcrack-based conductive film, a stretchable self-healing conductor with low hysteresis behavior was achieved. Furthermore, the conductor was used to record the electromyography (EMG) signals of human muscles, providing a promising path for stretchable electronic systems against mechanical damage and hysteresis.